Clinical Features and Quality of Life in End Stage Renal DiseasePatients Undergoing Hemodialysis Twice A Week Compared toThrice A Week - Imelda, Fitri; Susalit, Endang; Marbun, M Bonar M (UI Scholars Hub, 2017)
Introduction. National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NFK-KDOQI) recommends thrice weekly hemodialysis (HD) However, in Indonesia, most patients are given HD twice a week. Therefore it is necessary to investigate the clinical features and quality of life in End Stage Renal Disease (ESRD) patients undergoing twice-weekly HD. This study aimed to identify the clinical features and the quality of life in ESRD patients undergoing hemodialysis twice a week. Methods. A cross-sectional study was conducted in ESRD patients undergoing twice-weekly HD and thrice-weekly HD at Cipto Mangunkusumo Hospital and some private hospitals in Jakarta. Blood samples were obtained for laboratory examination. Meanwhile, quality of life were assessed by using Kidney Disease Quality of Life (KDQOL-SF 36). Results. A total of 80 subjects were included in this study, most of them were male and over 50 years old. Some clinical features were significantly higher in twice-weekly HD patients compared to thrice-weekly HD patients. Those features were Interdialytic Weight Gain (IDWG) (mean 4.91% (SD 1.52) and 3.82% (SD 1.28); p= 0.002); albumin (mean 4.05 mg/dl (SD 0.26) and 3.86 mg/dl (SD 0.48); p= 0.027); transferrin saturation (median 25.5% (range 12.0 to 274.0) and 21.95% (5.8 to 84.2); p= 0.004); phosphate level (mean 5.82 mg/dl (SD 1.68) and 5.82 mg/dl (SD 1.68); p= 0.026. Meanwhile, Total Iron Binding Capacity (TIBC) was significantly higher in thrice-weekly HD patients (mean 235.20 μg/dl (SD 55.72) and 273.73 μg/dl (SD 58.29 SB); p= 0.004). Approximately, 68% of twice-weekly HD reached Kt/V >1.8 and 93.3% of thrice-weekly HD reached Kt/V >1.2. Quality of life between the two groups was not significant either on Physical Componet Score (PCS) (p= 0.227), Mental Component Score (MCS) (p= 0.247), and Kidney Disease Component Score (KDCS) (p= 0.889). Conclusions. There are statistically significant differences between clinical features of twice-weekly HD and thrice-weekly HD on examination of IDWG, albumin, transferrin saturation, and phosphate levels which are higher in twice-weekly HD. Whereas, TIBC is higher in thrice-weekly HD group. Meanwhile, the patients quality of life in both groups showed no statistically significant differences.